2016
DOI: 10.1103/physrevb.94.205116
|View full text |Cite
|
Sign up to set email alerts
|

Ru2NbGa : A Heusler-type compound with semimetallic characteristics

Abstract: The Heusler-type compound of Ru 2 NbGa has been successfully synthesized. X-ray analysis confirms that Ru 2 NbGa crystallizes in a cubic L2 1 structure. The electronic properties of Ru 2 NbGa have been characterized by means of the transport and nuclear magnetic resonance (NMR) measurements. The temperature dependence of the electrical resistivity exhibits a typical semimetallic behavior. The NMR spin-lattice relaxation rate shows activated behavior at higher temperatures, attributing to the thermally excited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…Due to its finite residual resistivity at low temperatures, this material should be classified as a semimetal. Similar ρ(T ) features have been found in other ruthenium-based semimetallic Heusler compounds such as Ru 2 NbGa [28]. The activated transport behavior observed in Ru 2 TaAl can be realized as the thermally excited carriers across the pseudogap near E F , in analogy to the case of Ru 2 NbGa.…”
Section: A Electrical Transport and Thermoelectric Propertiessupporting
confidence: 75%
See 1 more Smart Citation
“…Due to its finite residual resistivity at low temperatures, this material should be classified as a semimetal. Similar ρ(T ) features have been found in other ruthenium-based semimetallic Heusler compounds such as Ru 2 NbGa [28]. The activated transport behavior observed in Ru 2 TaAl can be realized as the thermally excited carriers across the pseudogap near E F , in analogy to the case of Ru 2 NbGa.…”
Section: A Electrical Transport and Thermoelectric Propertiessupporting
confidence: 75%
“…Whereas, the GW methods [57], by calculating dynamically screened Coulomb interaction (W ) and Green's functions (G), have included the many-body interaction and thus will produce reliable band structures. Taking our previous studies related to Ru 2 NbGa as an example [28], the band structures obtained from DFT frameworks [Perdew-Burke-Ernzerhof (PBE) and HSE06) [58,59] are controversial while the results obtained from the GW 0 approximation [60] using either PBE or HSE06 initial wave functions have yielded consistent and reliable band structures. Based on the previous work [28], we have performed the first-principles total-energy calculations with GW 0 or G 0 W 0 corrections [60,61] for the band gaps using PBE initial wave functions.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…Since then, many studies have been dedicated to investigate the electronic and magnetic properties of ternary and quaternary full-Heusler compounds. It has been revealed that full-Heusler compounds exhibit a variety of electronic properties; they exhibit the properties of semiconductors [9][10][11][12][13][14][15][16][17][18], spingapless semiconductors (SGSs) [19][20][21][22][23][24][25][26], semimetals [27][28][29], metals [30][31][32][33][34] and half-metals (HMs) [32,. Considering the magnetic properties, they have been reported to exhibit nonmagnetism [9][10][11][14][15][16][17][18], ferromagnetism [12, 19-24, 30-33, 36-46, 48-58, 61-66, 68-78], ferrimagnetism [13,30,35,47,59,60,67] and antiferromagnetism [25,26,34].…”
Section: Crystal Structures and Magnetic Properties Of Full-heusler Cmentioning
confidence: 99%
“…This valence electron count (VEC) is frequently used to classify different groups of Heuslers. For example, for VEC = 24 semimetallic behavior is expected 15 with vanishing net magnetic moment 16 22 . Adding three electrons to the system (VEC = 27) often reveals superconductivity, including the Heusler compounds containing magnetic rare earth metals, i.e.…”
Section: Introductionmentioning
confidence: 99%